The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/cncr.27888
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative BRAF(V600E) mutation screening is unlikely to alter initial surgical treatment of patients with indeterminate thyroid nodules

Abstract: BACKGROUND: Preoperative B-type Raf kinase Val600Glu mutation, or BRAF(V600E), analysis has been proposed as a tool to guide initial surgery for indeterminate thyroid nodules. This study sought to determine if cytologic markers of malignancy are associated with the BRAF(V600E) mutation and if preoperative BRAF(V600E) testing would alter the initial management of patients with indeterminate nodules. METHODS: Patients who underwent surgery for a thyroid nodule between 2003 and 2012 at a tertiary care center were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 40 publications
3
43
0
1
Order By: Relevance
“…As this is not the case, it is unlikely that the decrease in the SFM call rate is solely attributable to cytopathologist factors. An alternative explanation could be that the rate of BRAF mutation-associated PTC is increasing [35], and the classical morphological findings in PTC are more pronounced in these tumors [36]. While there is no evidence in this retrospective review to test such a hypothesis, the influence of such environmental and epidemiological factors on the morphology and the performance of FNA in the thyroid cannot be eliminated and may have potential indications for the future of ancillary test development and use.…”
Section: Discussionmentioning
confidence: 49%
“…As this is not the case, it is unlikely that the decrease in the SFM call rate is solely attributable to cytopathologist factors. An alternative explanation could be that the rate of BRAF mutation-associated PTC is increasing [35], and the classical morphological findings in PTC are more pronounced in these tumors [36]. While there is no evidence in this retrospective review to test such a hypothesis, the influence of such environmental and epidemiological factors on the morphology and the performance of FNA in the thyroid cannot be eliminated and may have potential indications for the future of ancillary test development and use.…”
Section: Discussionmentioning
confidence: 49%
“…BRAF is not present in FTC and infrequent in the FVPTC (around 25% exhibit a BRAF mutation), and therefore, BRAF is a mutation rarely found in thyroid nodules with indeterminate cytology (24,25). This also reflects the sensitivity that our pathologists have for the typical nuclear features of PTC, which are more frequently present in tumors with a mutated BRAF, and therefore classified as malignant by cytology (26). In our series, 58% of the FVPTC (n = 11) had a PAX/PPARG rearrangement or a RAS mutation (one of them in combination with a RET/PTC1 Table 5 Characteristics of "true-positive," "false-positive," and "false-negative" nodules.…”
Section: Discussionmentioning
confidence: 90%
“…Atypical thyroid follicular cells, on the other hand, display numerous morphologies that may reflect underlying molecular epidemiology of the disease more than the quality of the cytopathology lab. For example, in 1 recent study, aspirates from BRAF- mutated classical PTC more likely showed the classic diagnostic features than aspirates from wild-type BRAF classic PTC [21]. If this holds in larger studies, it would indicate that the malignancy call rate may simply reflect the institutional BRAF mutation prevalence than the skill of the CT.…”
Section: Discussionmentioning
confidence: 99%